ANALISIS YURIDIS PELAKSANAAN TUGAS POKOK PENGELOLA DOMAIN INTERNET INDONESIA - Timoteus Natanael Sirait; Jimmy BP Simangungsong (Magister Hukum Universitas HKBP Nommensen, 2020)
PANDI (Indonesian Internet Domain Manager) Special authority is given to manage Indonesian domain names on the basis of law and their authority is stipulated in Law No. 23 of 2013 concerning Domain Name Management. PANDI's failure has been considered since the domain dispute between (bmw.co.id) and (bmw.id). There is no synchronization between domian (.co.id and .id) under the authority of PANDI. This research uses descriptive qualitative method.Qualitative method is a research method which in nature provides an explanation using analysis. In practice, this method is subjective in that the research process is more visible and tends to focus more on the theoretical foundation, with research methods aimed at explaining an event that is happening now and in the past. Domain is, the address on the internet that contains electronic data information, which can be accessed anywhere with an internet network on the website, the domain is needed to accelerate the development of information and communication and also in material and non-material transactions, there are many things that must be addressed regarding supervision Several Indone domains between: There is a need for firmer supervision by PANDI in terms of synchronization between dominance (.co.id) and (.id). There needs to be a synchronization between Government Regulation on Communication andInformation number 23 of 2013 concerning the management of Indonesian domain names, with law no. 20 of 2016 on Trademarks and Act No. 19 of 2016 amending the Law No. 11 of 2018 on Information and Electronic Transactions There needs to be a revision of Law No. 23 of 2013 concerning Management of the name Domaian Indonesia. The need for new legal policies that can provide a deterrent effect on crime in the field of cyber-specific domains. To avoid the many problems that will arise in the future about the Indonesian Domain some of the above need to be executed more quickly.